Impact of fiber chromatic dispersion on the BER performance of an optical CDMA IM/DD transmission system - Majumder, Satya Prasad; Azhari, A.; Abbou, F. M. (IEEE, 2005)
A theoretical analysis is presented to evaluate the impact of fiber chromatic dispersion on the bit-error-rate (BER) performance of a direct sequence optical code-division multiple-access (OCDMA) system with intensity modulation direct detection transmission link using sequence inverse keying optical correlator operating at 10 Gchip/s. The numerical results show that the system suffers a power penalty of 3.48 dB corresponding to chromatic dis persion index, gamma = 0.3 for seven-chip m-sequence, at a BER of 10(-9). It is further noticed that the number of simultaneous users are limited to 14 for gamma = 0.1 and 10 for gamma = 0.3, for 31-chip gold sequence, at 6-dg power penalty.